2019
DOI: 10.1088/2057-1976/ab36ea
|View full text |Cite
|
Sign up to set email alerts
|

Higher order analysis of time-resolved proton radiographs

Abstract: We demonstrate the potential of analyzing the higher order moments of time-resolved proton radiographic signals to generate images that show internal structures not visible in standard waterequivalent thickness (WET) images. Using a single detector distal to the patient, proton transmission images were acquired using a scintillating screen coupled to a CCD camera, with the beam range modulated using a small dedicated range modulator wheel. The variation of dose with time to a given pixel is referred to as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This is due to significant range mixing which limits the achievable accuracy RSP. In this context, we highlight a recent study by Doolan et al (2019) which showed that range mixing information can be retrieved from a statistical analysis of time-resolved dose signals. This technique was developed in the context of proton radiography using time-resolved dosimetry technique.…”
Section: Discussion and Outlookmentioning
confidence: 93%
“…This is due to significant range mixing which limits the achievable accuracy RSP. In this context, we highlight a recent study by Doolan et al (2019) which showed that range mixing information can be retrieved from a statistical analysis of time-resolved dose signals. This technique was developed in the context of proton radiography using time-resolved dosimetry technique.…”
Section: Discussion and Outlookmentioning
confidence: 93%